Metabolic danger signals, uric acid and ATP, mediate inflammatory cross-talk between hepatocytes and immune cells in alcoholic liver disease. Issue 2 (1st May 2015) - Petrasek, Jan; Iracheta-Vellve, Arvin; Saha, Banishree; Satishchandran, Abhishek; Kodys, Karen; Fitzgerald, Katherine A; Kurt-Jones, Evelyn A; Szabo, Gyongyi
Abstract : Uric acid and ATP from damaged hepatocytes activate IL-1β, a signature inflammasome-dependent cytokine crucial in the pathogenesis of alcoholic liver disease. Abstract: Inflammation defines the progression of ALD from reversible to advanced stages. Translocation of bacterial LPS to the liver from the gut is necessary for alcohol-induced liver inflammation. However, it is not known whether endogenous, metabolic danger signals are required for inflammation in ALD. Uric acid and ATP, 2 major proinflammatory danger signals, were evaluated in the serum of human volunteers exposed to a single dose of ethanol or in supernatants of primary human hepatocytes exposed to ethanol. In vitro studies were used to evaluate the role of uric acid and ATP in inflammatory cross-talk between hepatocytes and immune cells. The significance of signaling downstream of uric acid and ATP in the liver was evaluated in NLRP3-deficient mice fed a Lieber-DeCarli ethanol diet. Exposure of healthy human volunteers to a single dose of ethanol resulted in increased serum levels of uric acid and ATP. In vitro, we identified hepatocytes as a significant source of these endogenous inflammatory signals. Uric acid and ATP mediated a paracrine inflammatory cross-talk between damaged hepatocytes and immune cells and significantly increased the expression of LPS-inducible cytokines, IL-1β and TNF-α, by immune cells. Deficiency of NLRP3, a ligand-sensing component of the inflammasome recognizing uric acid and ATP, prevented the development of alcohol-induced liver inflammation in mice and significantly ameliorated liver damage and steatosis. Endogenous metabolic danger signals, uric acid, and ATP are involved in inflammatory cross-talk between hepatocytes and immune cells and play a crucial role in alcohol-induced liver inflammation.